Microplastics in The Atmosphere and Their Interaction with Biological Systems Through Systematic Literature and Scoping Reviews - Mohd Noor, Syazwaana; Yusuf, Sara Yasina; Mohamed, Mohd Rosiskada; Dewika Naidu; Nor Ruwaida Jamian (International Journal of Integrated Engineering, 2026)
Microplastics in the biosphere have emerged as a pressing environmental and public health concern owing to their widespread occurence and interactions with biological systems. This systematic review investigates the occurrence, transmission mechanisms, and health implications of airborne microplastics. The study applies the PRISMA framework and advanced search strategies across the Scopus and Web of Science databases, resulting in the selection of 35 primary studies. These studies were synthesized into three thematic categories: (1) Characterization of Microplastics in Various Environments, (2) Airborne Transmission and Aerosolization Mechanisms, and (3) Health Implications and Biological Interactions. The first theme highlights the widespread distribution and diversity of microplastics, particularly fibers and fragments, across indoor and outdoor environments. The second theme examines the pathways through which microplastics become airborne, with a focus on the influence of environmental factors such as wind, humidity, and human activities on their dispersion. The third theme explores the potential health consequences of inhaled microplastics, including respiratory complications and their interactions with microbial communities. This review underscores the critical need for robust monitoring systems, stricter regulatory measures, and heightened public awareness to address the escalating risks posed by airborne microplastic pollution. The findings call for interdisciplinary research to better understand the dynamics of microplastics in the atmosphere and to develop effective mitigation strategies to safeguard ecosystems and human health.